Tuberculosis Treatment Outcomes in Brazil: Different Predictors for Each Type of Unsuccessful Outcome. (5th July 2022) - Ridolfi, Felipe; Peetluk, Lauren; Amorim, Gustavo; Turner, Megan; Figueiredo, Marina; Cordeiro-Santos, Marcelo; Cavalcante, Solange; Kritski, Afrânio; Durovni, Betina; Andrade, Bruno; Sterling, Timothy R; Rolla, Valeria; et al.
Abstract: Background: Successful tuberculosis (TB) treatment is necessary for disease control. The World Health Organization (WHO) has a target TB treatment success rate of ≥90%. We assessed whether the different types of unfavorable TB treatment outcome had different predictors. Methods: Using data from Regional Prospective Observational Research for Tuberculosis-Brazil, we evaluated biological and behavioral factors associated with each component of unsuccessful TB outcomes, recently updated by WHO (death, loss to follow-up [LTFU], and treatment failure). We included culture-confirmed, drug-susceptible, pulmonary TB participants receiving standard treatment in 2015–2019. Multinomial logistic regression models with inverse probability weighting were used to evaluate the distinct determinants of each unsuccessful outcome. Results: Of 915 participants included, 727 (79%) were successfully treated, 118 (13%) were LTFU, 44 (5%) had treatment failure, and 26 (3%) died. LTFU was associated with current drug-use (adjusted odds ratio [aOR] = 5.3; 95% confidence interval [CI], 3.0–9.4), current tobacco use (aOR = 2.9; 95% CI, 1.7–4.9), and being a person with HIV (PWH) (aOR = 2.0; 95% CI, 1.1–3.5). Treatment failure was associated with PWH (aOR = 2.7; 95% CI, 1.2–6.2) and having diabetes (aOR = 2.2; 95% CI, 1.1–4.4). Death was associated with anemia (aOR = 5.3; 95% CI, 1.4–19.7), diabetes (aOR = 3.1; 95% CI, 1.4–6.7), and PWH (aOR = 3.9; 95% CI, 1.3–11.4). Direct observed therapy was protective for treatment failure (aOR = 0.5; 95% CI, .3–.9) and death (aOR = 0.5; 95% CI, .2–1.0). Conclusions: The treatment success rate was below the WHO target. Behavioral factors were most associated with LTFU, whereas clinical comorbidities were correlated with treatment failure and death. Because determinants of unsuccessful outcomes are distinct, different intervention strategies may be needed to improve TB outcomes. Abstract : High rates of unsuccessful treatment outcomes in a cohort of patients with tuberculosis in Brazil. Behavioral factors (drug and alcohol use) influenced losses to follow-up and clinical comorbidities (human immunodeficiency virus, diabetes, and anemia) affected treatment failure and death.